Cultura visual y crisis de la experiencia - Castañares, Wenceslao (CIC. Cuadernos de Información y Comunicación, 2007)
Even if saying that our era is “ocular-centric” is perhaps an exaggeration, it is sure that the visual image is a central place of our culture. If we talk about visual culture we must talk also about the diverse scopic regimes (forms of seeing and watching), which implicates a consideration historical about the role of the image in culture and, in the end, of the modifications in experience in relationship with the different forms of using it. From this point of view, in this paper there are two questions analysed. Firstly to define this new form of representation, so typical of our era, so called “virtual reality”, opposite to the concepts of reality and actuality. Secondly, to make clear in what sense is the experience possible, and over all, how the new forms of representation put it in crisis.